Métodos de inoculação e avaliação da resistência de genótipos de soja à Sclerotinia sclerotiorum - Sagata, Érika (2010)
Soybean stem white rot, caused by Sclerotinia sclerotiorum, occurs in more than one million hectares in Brazil. This disease should be managed by integrated control methods, including genetic resistance. This study evaluated and developed a reliable method for the selection of soybean genotypes resistant to stem white rot. The work was based on rating inoculations on the stem. The methods evaluated consisted of different inoculation sites in the plant, wounding or not or cutting the stem of the plants, and inoculating PDA disks containing fungal mycelium. The tests were conducted in two different environments, a controlled one, where plants were grown in a greenhouse and brought into the laboratory to be inoculated and incubated in a growth chamber where the temperature is favorable for fungal growth, and a field, where the pathogen is subjected to adverse environment conditions. Spearman´s coefficients of rank correlation was used to measure the correspondence between ranks of cultivar and ranks of the same cultivars in field experiments to establish the best inoculation method. It was observed that temperature growth conditions, and inoculation method may affect the selection of resistant soybean genotypes against stem rot. The best method to evaluate soybean resistance was by wound inoculating the middle third of the plant when the plants were at the end of flowering and early grain filling, with PDA disks and evaluating 14 days later. This method was rs = 0.86, and the variety that can be considered as resistance standard in other studies was Emgopa 316, while the susceptible standards were BRSMG Garantia and BRSMG68 Vencedora.